High Pressure Rheology of Lubricants (Part 2) - Masato Kaneko (Tribology Online, 2024)
In elastohydrodynamic lubrication (EHL) theory published in 1962, Dowson et al. derived a density pressure relational equation. Therefore, it seemed that this equation could be utilized as an estimation equation of the density term of the viscosity pressuretemperature-density linear equation of Part 1 of the paper. However, since the temperature function is not included in the equation, the calculated value at 40°C is in good agreement with the measured value, but in the high temperature range, the calculated value found large deviation from the measured value. Therefore, introduction of temperature function into the equation was studied, and density-pressure-temperature relational equation was newly derived. In this result, it became possible to estimate the high pressure density at each temperature, and it became possible to utilize as the estimation equation of the density term of the 1st report. And it was found that the linear equation can also be applied to the ASME report data up to around 1 GPa. Incidentally, the slope a of the linear equation is a characteristic constant of the lubricant related to the high pressure density and the 1 + 1/b value obtained from the intercept b indicates the maximum density ratio.